Mapping travel : the origins and conventions of western journey maps - Dym, Jordana, 1967- (Leiden, The Netherlands : Brill, 2021)
Drawing on a thousand years of European travel writing and mapmaking, Dym suggests that after centuries of text-based itineraries and on-the spot directions guiding travelers and constituting their reports, maps in the fifteenth century emerged as tools for Europeans to support and report the results of land and sea travel. With each succeeding generation, these linear journey maps have become increasingly common and complex, responding to changes in forms of transportation, such as air and motor car 'flight' and print technology, especially the advent of multi-color printing. This is their story.
Abstract -- Keywords -- Introduction -- Travel Writing and Mapping: Definitions and Sources -- Historiography -- Before the Line: Points and Lists -- Early Journey Maps: From Implicit to Explicit Lines -- Conventions of the Journey Map: Lines, Space and Time -- Journey Maps in the Eighteenth Century: Up and Down the Line -- Journey Maps in the Steam Age: Retracings, Erasure and Colored Lines -- The Leap from the Page to the Screen -- Conclusion -- Acknowledgments -- References.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on October 26, 2021).
eBooks on EBSCOhost
Keywords: Cartography -- Europe -- History; Early maps -- Europe -- History; Europe -- Description and travel; Cartographie -- Europe -- Histoire; Cartes anciennes -- Europe -- Histoire; Europe -- Descriptions et voyages; Cartography; Early maps; Travel; Europe; History